Geriatric assessment in older adults with non-Hodgkin lymphoma: A Young International Society of Geriatric Oncology (YSIOG) review paper. Issue 5 (June 2022) - Akhtar, Othman Salim; Huang, Li-Wen; Tsang, Mazie; Torka, Pallawi; Loh, Kah Poh; Morrison, Vicki A.; Cordoba, Raul
Abstract: Non-Hodgkin lymphoma (NHL) is a disease of older adults, with a median age at diagnosis of 67 years. Treatment in older adults with NHL is challenging. The aging process is associated with a decline in functional reserve that varies among individuals, and results in an increasing risk of treatment-related toxicity and mortality. Chronological age and performance status fail to capture the multidimensional and heterogeneous nature of the aging process. A geriatric assessment (GA) screens multiple geriatric domains and provides a more accurate assessment of functional reserve. Several abbreviated GA tools have been developed for use in oncology clinics and help identify patients at high risk for chemotherapy-related toxicity and mortality. In this review, we explore GA tools validated for use in patients with NHL. We discuss the evidence behind GA–guided treatment in NHL and present a suggested approach to assessing frailty in this patient population.